Acute kidney injury in two children caused by renal hypouricaemia type 2 - Stibůrková, Blanka; Šebesta, Ivan; Marinaki, Anthony M; Sebesta, Ivan (Pediatric nephrology, 2012)
BACKGROUND: Renal hypouricaemia is a heterogeneous inherited disorder characterized by impaired tubular uric acid transport with severe complications, such as acute kidney injury and nephrolithiasis. Type 1 is caused by a loss-of-function mutation in the SLC22A12 gene (OMIM #220150), while type 2 is caused by defects in the SLC2A9 gene (OMIM #612076). CASE-DIAGNOSIS/TREATMENT: The cases of two children, a 12- and a 14-year-old boy with acute kidney injury (proband 1: urea 9.4 mmol/l, creatinine 226 μmol/l; proband 2: urea 11.7 mmol/l, creatinine 202 μmol/l) are described. Both are offspring of nonconsanguineous couples in the UK. The concentrations of serum uric acid were consistently below the normal range (0.03 and 0.04 mmol/l) and expressed as an increase in the fractional excretion of uric acid (46 and 93 %). CONCLUSIONS: A sequencing analysis of the coding region of uric acid transporters SLC22A12 and SLC2A9 was performed. Analysis of genomic DNA revealed two unpublished missense transitions, p.G216R and p.N333S in the SLC2A9 gene. No sequence variants in SLC22A12 were found. Our findings suggest that homozygous and/or compound heterozygous loss-of-function mutations p.G216R and p.N333S cause renal hypouricaemia via loss of uric acid absorption and do lead to acute kidney injury.
Keywords: Renal Tubular Transport, Inborn Errors; močové kameny; Glucose Transport Proteins, Facilitative; Uric Acid; Adolescent; DNA Mutational Analysis; mutační analýza DNA; dítě; Mutation, Missense; mužské pohlaví; proteiny usnadňující transport glukosy; vrozené poruchy tubulárního transportu; kyselina močová; lidé; akutní poškození ledvin; Child; Humans; missense mutace; Acute Kidney Injury; Male; mladiství; Urinary Calculi